2014
DOI: 10.1371/journal.pone.0103510
|View full text |Cite
|
Sign up to set email alerts
|

Passport Officers’ Errors in Face Matching

Abstract: Photo-ID is widely used in security settings, despite research showing that viewers find it very difficult to match unfamiliar faces. Here we test participants with specialist experience and training in the task: passport-issuing officers. First, we ask officers to compare photos to live ID-card bearers, and observe high error rates, including 14% false acceptance of ‘fraudulent’ photos. Second, we compare passport officers with a set of student participants, and find equally poor levels of accuracy in both gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
322
3
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 263 publications
(347 citation statements)
references
References 18 publications
19
322
3
3
Order By: Relevance
“…In a recent study of professional fingerprint examiners, participants could skip comparison decisions on the basis that they did not provide sufficient evidence for identification [35]. Although this approach inhibits the measurement of underlying perceptual skill [35,36], these types of decisions are critical in minimizing costly workplace errors, and recent work suggests that forensic examiners are skilled in these types of judgements [11]. Thus, our results provide an estimate of the perceptual abilities of facial forensic examiners that can serve as a benchmark for future tests of identification accuracy in standard forensic practice, and for computer-based face recognition systems that support this practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study of professional fingerprint examiners, participants could skip comparison decisions on the basis that they did not provide sufficient evidence for identification [35]. Although this approach inhibits the measurement of underlying perceptual skill [35,36], these types of decisions are critical in minimizing costly workplace errors, and recent work suggests that forensic examiners are skilled in these types of judgements [11]. Thus, our results provide an estimate of the perceptual abilities of facial forensic examiners that can serve as a benchmark for future tests of identification accuracy in standard forensic practice, and for computer-based face recognition systems that support this practice.…”
Section: Discussionmentioning
confidence: 99%
“…In suboptimal capture conditions when environmental factors are unconstrained, such as when matching between CCTV footage and high-quality mug-shots, performance can approach chance [10]. Moreover, in field tests conducted outside of the laboratory, professional police officers and passport officers make the same number of face matching errors as standard groups of student participants [10,11], despite performing face matching as part of their daily work.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent report, White, Kemp, Jenkins, Matheson and Burton (2014) showed that even trained passport control officers are not better at matching identities than lay persons, such as university students. The findings reviewed earlier suggest that people with exceptionally good unfamiliar face‐processing skills would be particularly useful in a court of law when it is uncertain whether a defendant's identity matches a person captured on CCTV footage.…”
mentioning
confidence: 99%
“…Expert recognition is disrupted when images are presented in a novel, inverted orientation (e.g., Crump, Logan & Kimbrough, 2010;Curby, Glazek, Gauthier, 2009;Diamond & Carey, 1986;Thompson, 1980), or when presented in a novel configuration (Gauthier & Tarr, 1997;Young, Hellawell & Hay, 1987), and we are generally not as fast, or as accurate, at recognising less familiar objects, including novel face identities (Bruce, 1982;Clutterbuck & Johnston, 2002, 2004, 2005White, Burton, Jenkins & Kemp, 2014)-we are, of course, novices with novel objects. As a novice, recognition is more deliberative and slow (Newell & Rosenbloom, 1981), novices can attend to parts of objects (Young et al, 1987), and they tend to rely more on verbalisable rules Gauthier & Curby, 2005), or algorithms (Logan, 1988).…”
Section: Overviewmentioning
confidence: 99%
“…prints Thompson, Tangen & McCarthy, 2013), and particular groups of facial recognition examiners, whose task it is to compare unfamiliar faces for identity, also display superior performance compared to novices (White, Phillips, Hahn, Hill & O'Toole, 2015; although see White, Kemp, Jenkins, Matheson & Burton, 2014). These examiners face a formidable recognition task day to day.…”
Section: Novel Object Recognition In Forensic Sciencementioning
confidence: 99%